Presynaptic GABAB receptors inhibit vomeronasal nerve transmission to accessory olfactory bulb mitral cells - Weiss, Jan; Zufall, Frank (Frontiers in Cellular Neuroscience, 2023)
Vomeronasal sensory neurons (VSNs) recognize pheromonal and kairomonal semiochemicals in the lumen of the vomeronasal organ. VSNs send their axons along the vomeronasal nerve (VN) into multiple glomeruli of the accessory olfactory bulb (AOB) and form glutamatergic synapses with apical dendrites of mitral cells, the projection neurons of the AOB.Juxtaglomerular interneurons release the inhibitory neurotransmitter γ-aminobutyric acid (GABA). Besides ionotropic GABA receptors, the metabotropic GABAB receptor has been shown to modulate synaptic transmission in the main olfactory system. Here we show that GABAB receptors are expressed in the AOB and are primarily located at VN terminals.Electrical stimulation of the VN provokes calcium elevations in VSN nerve terminals, and activation of GABAB receptors by the agonist baclofen abolishes calcium influx in AOB slice preparations. Patch clamp recordings reveal that synaptic transmission from the VN to mitral cells can be completely suppressed by activation of GABAB receptors. A potent GABAB receptor antagonist, CGP 52432, reversed the baclofen-induced effects. These results indicate that modulation of VSNs via activation of GABAB receptors affects calcium influx and glutamate release at presynaptic terminals and likely balances synaptic transmission at the first synapse of the accessory olfactory system.